Analysis of the Performance of Islamic Commercial Banks in Indonesia in 2021-2023: Maqashid Sharia Index and Islamicity Performance Index Approach - Moch Anshori; Tachiyat (International Journal of Islamic Finance, 2025)
Background: The Islamic banking sector in Indonesia has seen rapid growth. To support this expansion, performance measurement methods adhering to Shariah principles are essential.Objectives: This study evaluates the performance of Islamic Commercial Banks (ICBs) in Indonesia using the Maqashid Syariah Index (MSI) and the Islamicity Performance Index (IPI).Novelty: Unlike previous studies, this research addresses gaps in prior findings and reexamines the alignment of Islamic banking practices with Shariah principles.Research Methodology / Design: A purposive sampling technique was employed to select 10 ICBs. The study adopts a quantitative approach using secondary data from financial reports and applies descriptive analysis to assess bank performance.Findings: The results reveal that many ICBs in Indonesia do not fully align with MSI or IPI metrics, indicating inconsistencies in achieving Shariah objectives.Implication: Further research with expanded sample sizes and refined methodologies is essential. Islamic banks must enhance the transparency and comprehensiveness of financial disclosures to better reflect Shariah compliance. Additionally, theoretical advancements are required to bridge gaps in current performance measurement frameworks.